Accurate configuration force evaluation via hp-adaptive discontinuous Galerkin finite element analysis. (July 2019) - Bird, Robert; Coombs, William M.; Giani, Stefano
Highlights: New domain independent configurational force calculation is proposed. Configurational force error bounded by a robust a posteriori error estimate. Exponential convergence of the configurational force is achieved with hp -adaptivity. Accurate benchmarks produced using the proposed configurational force calculation. Investigation and comparison of existing configurational calculation methods. Abstract: Engineers require accurate determination of the configurational force at the crack tip, and corresponding stress intensity factors, for fracture fatigue analysis and accurate crack propagation. However, obtaining highly accurate crack tip configuration force values is challenging with methods requiring knowledge of the stress field around the crack tip a priori . This paper proposes a method which aims to remove the necessity of knowing the stress field a priori whilst producing very accurate values of the configurational force at a static crack tip. The proposed method is demonstrated to be path independent and is combined with a robust a posteriori residual error estimator which is indicative of the accuracy of the configurational force calculation. This makes it possible to generate accurate values for the configurational force acting both perpendicular and parallel to the crack edges. Accuracies are achieved which are at least 10 4 times more accurate than other numerical methods which make no assumption about the local tip stress field. Therefore accurate benchmarks are determined in this paper for inclined, split and tree crack problems. In addition the new method is shown to obtain very similar values for the configurational force compared to results obtained using other methods which require knowledge of the stress field at the crack tip. The techniques presented in this paper open the door to configurational force-based methods being used for fatigue analysis.